Stearate-Induced Apoptosis in Human Pancreatic β-Cells is Associated with Changes in Membrane Protein Expression and These Changes are Inhibited by Oleate - Němcová-Fürstová, Vlasta; Balušíková, Kamila; Halada, Petr; Pavlíková, Nela; Šrámek, Jan; Kovář, Jan (Proteomics. Clinical applications, 2019)
PURPOSE: Lipotoxicity is implicated in type 2 diabetes pathogenesis. Its molecular mechanisms are not completely understood. The aim of this study is to identify new suspect proteins involved in pancreatic β-cell death induction by saturated fatty acids and its inhibition by unsaturated fatty acids. EXPERIMENTAL DESIGN: Employing 2DE analysis and subsequent western blot confirmation, the differences in membrane/membrane-associated protein expression in human β-cell line NES2Y are assessed during cell death induction by stearate and its inhibition by oleate. RESULTS: Induction of apoptosis by stearate is associated with significantly increased levels of Hsp90β, peroxiredoxin-1, and 14-3-3γ in the membrane fraction of NES2Y cells and significantly decreased levels of annexin A2, annexin A4, and reticulocalbin-2. All these changes are significantly inhibited by oleate co-application. No expression changes are detected after application of stearate together with oleate. Furthermore, the expression of reticulocalbin-2 is significantly decreased after stearate application also in the whole cell lysate. CONCLUSIONS AND CLINICAL RELEVANCE: Several membrane-associated proteins that could be related to pro- and anti-apoptotic signaling initiated by fatty acids in human pancreatic β-cells are identified. As far as we know, annexin A4, reticulocalbin-2, and 14-3-3γ represent novel molecules related to the effect of fatty acids on β-cell viability.
Keywords: apoptóza; Stearic Acids; buněčné linie; membrane protein; Apoptosis; beta-buňky; lidé; Oleic Acid; kyselina olejová; saturated fatty acid; unsaturated fatty acid; β-cell apoptosis; membránové proteiny; proteomics; Cell Line; regulace genové exprese; Insulin-Secreting Cells; Membrane Proteins; kyseliny stearové; Gene Expression Regulation; 2D electrophoresis; Humans